Recurrent midgut volvulus in an 83-year-old female. Issue 7 (23rd July 2021) - Kang, Lorna; Larson, Brandon; Barker, Shelly; Ma, Truong
Abstract: We present a rare case of recurrent primary midgut volvulus in an elderly female with an interesting intraoperative finding of an abnormally elongated small bowel mesentery. This patient presented with symptoms of obstruction, including nausea, vomiting and obstipation, similar to previous episodes of volvulus for which she underwent exploratory laparotomies and reduction of the volvulus. We describe a novel use for enteropexy in which we effectively shortened the small bowel mesentery in an effort to eliminate the source of recurrent volvulus. The patient's post-operative course was complicated by prolonged ileus requiring total parenteral nutrition. However, she had not developed signs or symptoms of bowel ischemia or recurrent volvulus at the time of this writing. Our findings suggest that enteropexy is an effective technique for preventing recurrent midgut volvulus primarily caused by abnormally elongated mesentery.